HUBUNGAN ANTARA PENGETAHUAN MASYARAKAT DAN PERAN PETUGAS KESEHATAN DENGAN SANITASI JAMBAN DI WILAYAH KERJA PUSKESMAS BATANG ASAI KABUPATEN SAROLANGUN TAHUN 2013 - Pirmansyah Pirmansyah; T. Samsul Hilal; Aris Munandar (Universitas Batanghari Jambi, 2014)
Excreta disposal is an important part of environmental sanitation, non-sanitary excreta disposal can result in negative impacts on the surrounding environment such as water, human and land. Besides it also could lead to a smell that can not be tolerated. In Jambi province of the results of a home inspection, it appears that the use of latrine coverage in 2011 was 68.72%. Family latrine coverage (Keep) healthy Sarolangun in 2011 only 60.16%. Lowest coverage contained in Batang Asai health center is 35.58%.This research is a quantitative study with cross-sectional design. The population in this study was the entire house that has a toilet with a sample size of 83 respondents, taken at random with a systematic random technique (Systematic Sampling). Data were collected using interviews and observations with research questionnaires. Data were analyzed using univariate and bivariate Chi-square test.Results of univariate analysis of the 83 respondents indicated that there is, as much as 60.2% of respondents have a sanitary latrine families who are not eligible, 54.2% of respondents have a poor knowledge, 57.8% of respondents said the role of health workers is not good. The results of the bivariate analysis showed no significant relationship between knowledge and the role of health workers to the family toilet sanitation.Keywords: Sanitary latrine family, the knowledge and the role of health workers.